LIKUIDITAS DAN PERMODALAN BANK MILIK PEMERINTAH SEBELUM DAN PADA MASA PANDEMI - Nengah Sukendri (Distribusi - Journal of Management and Business, 2021)
This study analyzes state-owned Bank liquidity and capital before and during the Covid-19 pandemic in terms of liquidity and capital. The approach used in this research is comparative quantitative research. The data used are banking financial reports before and during the pandemic with a research focus: Bank Rakyat Indonesia (BRI), Bank Mandiri, Bank Negara Indonesia (BNI), Bank Tabungan Negara (BTN). Before the analysis was carrying out, the Research Instrument Prerequisite Test carrying out using Kolmogorov-Smirnov, and the analysis technique in this study was using paired t-test analysis. The results showed a difference before and during the pandemic regarding state-owned bank liquidity and capital adequacy.